Optimal Stitch Forming Line Identification for Attaching Patches on Non-Developable Clothing Surfaces. (October 2021) - Suh, Hyo-Won; Ko, Hyeong-Seok
Abstract: In clothing design and manufacturing, the need to attach a foreground (such as an emblem or pocket) on the background (i.e., clothing surface) arises. For that, stitch forming line needs to be identified on the surface of the background that should be seamed with that of the foreground. Often, the shape of the background is non-developable thus the problem is not straightforward. In this paper we developed an optimization method to overlay the foreground on the background such that the planar deformation and the deformation variance of the foreground is minimized. We applied the optimization technique to various cases of developable and non-developable background cases and verified the optimization works as expected. Highlights: Stitch line of attachments on garment affects final quality of apparel. Stitching line identification of attachments is task requiring intricate skill. Overlaying an attachment on the surface of garment readily finds the stitch lines. Deformation minimizing overlaying of attachment on the surface of garment is achieved through energy minimizing optimization.